DETERMINAN HARGA SAHAM PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tasya Permata Putri (2022)
This research aims to find out whether there is influence from liquidity, solvency, profitability and market on stock prices. The object chosen by the author in this study is an infrastructure company listed on the Indonesia Stock Exchange using a sample of 42 companies during the 2017 - 2021 period. Furthermore, the author uses quantitative research methods to maximize the use of data and numbers to obtain accurate results. Moreover, the hypothesis in this study was tested with a significance level of 5%, using the Panel Data Regression Analysis Method with the EViews 12 computer program. The results found in this study were (1) there was no influence between liquidity and stock prices, (2) there was no influence between solvency and stock prices, (3) there is influence between profitability on stock prices, and (4) there is influence between the market on stock prices."